Uji Potensi Biogas dari Eceng Gondok (Eichhornia Crassipes) dan Campuran Limbah Jeroan Ikan Gabus (Channa Striata) Menggunakan Digester Anaerob secara Batch - Hernandes Sitorus Pane; Indah Widiastuti; Ace Baehaki (Universitas Sriwijaya, 2016)
The purpose of this research was to utilize water hyacinth biomass and sneakhead waste as substrats for biogas production as a renewable energy source by different treatment on substrate composition. This research used experimental method in anaerobic batch reactors with Liquid Displacement and Atomic Absorbtion methods using NaCl and NaOH solutions. The results in this research were analyzed by descriptive method. The observed parameters were rate and accumulation of biogas and methane production, and slurry’s parameters such as themperature, pH, BOD, COD, TS, VS, and C/N ratio. Results showed that the difference of substrates composition in reactor A produced the highest biogas and methane accumulation. Whereas in reactor B produced the highest methane percentage.